Assistive Technology as an aid to individuals with Autism Spectrum Disorder: A Systematic Literature Mapping - Siedler, Marcelo; Zen, Eliana; Cardoso, Rafael; Tavares, Tatiana (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
Assistive Technology (AT) is the research area focused on the investigation, development, and evaluation of resources and services focused on people with physical or cognitive limitations. Its pri- mary goal is to expand its users’ preserved skills. A target audience that can benefit from this study field is people with Autism Spectrum Disorder (ASD) since they may have several comorbidities. This work highlights a Systematic Literature Mapping (SLM) on AT for autistic people, which uses Information and Communication Technologies (ICTs) in its design. In this way, this paper details all the steps involved in this literature review, until reaching 47 closely related articles on the SLM’s main topic. From this analysis, the paper outlines an overview of the researched area, proposing a taxonomy that organizes the works according to 4 different clas- sifications: type of solution developed; degree of autism severity; the purpose of work; and age group. Finally, the article highlights trends and technological/methodological aspects observed during the analysis of these studies, in addition to identifying potential research gaps that can be explored as a work sequence.